The black hole of the camera : the films of Andy Warhol - Murphy, J. J., 1947- (University of California Press, 2012)
Andy Warhol, one of the twentieth century's major visual artists, was a prolific filmmaker who made hundreds of films, many of them--Sleep, Empire, Blow Job, The Chelsea Girls, and Blue Movie--seminal but misunderstood contributions to the history of American cinema. In the first comprehensive study of Warhol's films, J.J. Murphy provides a detailed survey and analysis. He discusses Warhol's early films, sound portraits, involvement with multimedia (including The Velvet Underground), and sexploitation films, as well as the more commercial works he produced for Paul Morrissey in the late 1960s and early 1970s. Murphy's close readings of the films illuminate Warhol's brilliant collaborations with writers, performers, other artists, and filmmakers. The book further demonstrates how Warhol's use of the camera transformed the events being filmed and how his own unique brand of psychodrama created dramatic tension within the works.
Keywords: Warhol, Andy, -- 1928-1987 -- Criticism and interpretation.; Warhol, Andy, -- 1928-1987; ART -- Individual Artists -- Artists' Books.; ART -- Individual Artists -- Essays.; ART -- Individual Artists -- Monographs.; Films.; Filmregie.; Regissörer.; Konstnärer.; PERFORMING ARTS / Film / General; Criticism, interpretation, etc.